Single visit biomimetic restoration with multilayered direct composite technique on maxillary central incisor - Alfajri; Farahanny, Wandania; Dennis (Universitas Airlangga, 2025)
Background: Biomimetic restoration with multilayered composite gives the highest aesthetic result with the least invasive tooth structure. The goal of these techniques is to restore teeth while closely mimicking the micro- and macrostructure, chromatic properties, and tooth symmetry of the original dentition. These techniques need extra instruments and the clinician's experience. Purpose: This case study aims to describe a technique for repairing anterior defects in just one appointment. Case: A 24-year-old man complained about the color, asymmetry, and fracture of his anterior teeth. However, he does not have much time to wait for the indirect restoration procedure. A single-visit treatment was preferred for this case. Case Management: A manual wax-up for the palatal index followed by multilayered composite restoration was nicely done in a single appointment. Defects in anterior teeth could be repaired in a single appointment using multilayer direct composite restoration. This method could effectively replicate the teeth's morphology, symmetry, micro-macro structure, and chromatic properties. The quick manual wax-up and layering steps are critical to this procedure. Discussion: Currently, direct restorations for anterior teeth are completed in three stages: incisal edge and palatal wall shaping; interproximal wall creation utilizing a pre-contoured matrix technology; and buccal surface application of multilayered composite. Multilayered direct composite restoration technique with manual palatal index can be an alternative procedure to create immediate natural-looking anterior restoration. This technique offered a reduction of chairside time in a single-stage appointment, laboratory cost savings, and more predictable results.